2008
DOI: 10.1159/000126078
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ocular Surface Side Effects of Topical Travoprost and Bimatoprost

Abstract: Purpose: To compare the subjective symptoms, conjunctival hyperemia, tearing response and conjunctival cytological changes secondary to topical administration of bimatoprost and travoprost for 6 months. Methods: Newly diagnosed primary open-angle glaucoma patients were randomly prescribed bimatoprost (35 cases) or travoprost (42 cases). Two patients in each group were excluded because they did not appear at their appointments regularly. Thus, 33 and 40 patients completed the study in the bimatoprost and travop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 64 publications
1
3
0
Order By: Relevance
“…The type and incidence of the treatment-related adverse events were in agreement with previous studies [34-37], with conjunctival hyperemia the most commonly reported ocular adverse event. It should be pointed out that, despite the relatively high overall incidence, the majority of reported hyperemia cases were trace or mild, and most of the patients with a hyperemia increase from baseline had only a 0.5-grade increment.…”
Section: Discussionsupporting
confidence: 90%
“…The type and incidence of the treatment-related adverse events were in agreement with previous studies [34-37], with conjunctival hyperemia the most commonly reported ocular adverse event. It should be pointed out that, despite the relatively high overall incidence, the majority of reported hyperemia cases were trace or mild, and most of the patients with a hyperemia increase from baseline had only a 0.5-grade increment.…”
Section: Discussionsupporting
confidence: 90%
“…The present study aimed to explore another type of stimulation on this CALT structure, namely of toxic origin such as that induced by the well-recognized contact irritant BAK, and to compare it with the effects of various BAK-containing antiglaucomatous eyedrops. We mainly focused on the main prostaglandin analogs (PGA) currently available worldwide, as belonging to the major family of antiglaucomatous drugs and as they present different biochemical properties and irritant features [15], [16]. Interestingly, these eyedrops differ from one another in their BAK concentration and may provide interesting comparative information on CALT involvement.…”
Section: Introductionmentioning
confidence: 99%
“…The mean reduction in Schirmer's was greater in the timolol group at both 3 months and 6 months and it was statistically significant. 17 The rose bengal scores continued to rise over the period of 6 months in the timolol group. In the bimatoprost group, increase in scores were seen later towards the 6 months.…”
Section: Discussionmentioning
confidence: 89%